Effects of temperature and of heat shock on the expression and action of the colicin A lysis protein. - Cavard, D (1995)
At low temperature, the synthesis of the colicin A lysis protein in Escherichia coli was slowed down, and consequently its functioning was retarded. The rates were restored when the bacteria were shifted for 10 min to 42 degrees C, except in an rpoH mutant, suggesting that one or more proteins regulated by sigma 32 is necessary for expression of colicin A lysis protein.